Limits and opportunities for conducting quantitative and qualitative research in terms of the societies in transition (the example of Bulgaria) - Rusinova, Evgeniya (Qualitative and Quantitative Methods in Libraries, 2017)
Societies in transition pose to the libraries some serious problems, which are new to them (compared to the previous period). The first problem concerns the financing of libraries. Along with this there is organizational change. This directly affects the relationship between the institution and library users. The situation which is created greatly hampers the study of library users and the environment. As a result, the introduction of marketing and measurement of the quality of library work is impeded. The report puts several major emphases on: 1. The factors that determine the choice of approaches and methods of library research; 2. The modalities through which quantitative and qualitative research can be applied ; 3. The successful cases of combined use of QQM and the possibility of practical application of the results on a local and national level.